Characterization of in vitro antagonistic activity of Lactobacillus helveticus DLBSA201 and DLBSA202 against Escherichia coli 0157:H7 - TJANDRAWINATA, Raymond R.; KARTAWIJAYA, Medicia; HARTANTI, Apriliana Wahyu; HADIANTA, Randi (Food Science and Technology, 2023)
Lactobacillus helveticus DLBSA201 and DLBSA202 were investigated for their potential probiotic traits and protective effects against Escherichia coli O157:H7. The survival rate of DLBSA201 and DLBSA202 after being exposed to acid and bile salt was relatively high, although no bile salt hydrolase activity was detected. Both strains also demonstrated an outstanding ability to adhere to intestinal epithelial cells. A combination of DLBSA201 and DLBSA202 could interfere with the growth of E. coli O157:H7. Furthermore, DLBSA201 and DLBSA202 also exhibited the ability to remove pre-adhered E. coli O157:H7 on intestinal cells. Those strains were able to lower pro-inflammatory genes [TLR-4, tumor necrosis factor-α (TNF-α), and interleukin-8 (IL-8)] in lipopolysaccharides (LPS)-treated intestinal epithelial cells. In addition, the upregulation of occludin and ZO-1 genes by DLBSA201 and DLBSA202 also ameliorates the disruption of the intestinal barrier caused by LPS. The above results suggest that DLBSA201 and DLBSA202 association appear as promising probiotic candidates with the potential to prevent and treat intestinal disease caused by E. coli O157:H7.